Bone mesenchymal stem cell-derived exosomes prevent hyperoxia-induced apoptosis of primary type II alveolar epithelial cells in vitro - Yang, Wei; Huang, Chao; Wang, Wenjian; Zhang, Baozhu; Chen, Yunbin; Xie, Xinlin (PeerJ, 2022)
Background The presence of alveolar epithelial type II cells (AECIIs) is one of the most important causes of bronchopulmonary dysplasia (BPD). Exosomes from bone mesenchymal stem cells (BMSCs) can reduce hyperoxia-induced damage and provide better results in terms of alveolar and pulmonary vascularization parameters than BMSCs. Currently, intervention studies using BMSC-derived exosomes on the signaling pathways regulating proliferation and apoptosis of alveolar epithelial cells under the condition of BPD have not been reported. This study investigated the effects of rat BMSC-derived exosomes on the proliferation and apoptosis of hyperoxia-induced primary AECIIs in vitro. Methods The isolated AECIIs were grouped as follows: normal control (21% oxygen), hyperoxia (85% oxygen), hyperoxia+exosome (20 µg/mL), hyperoxia+exosome+LY294002 (PI3K/Akt inhibitor, 20 µM), and hyperoxia+exosome+rapamycin (mTOR inhibitor, 5 nM). We used the PI3K/Akt inhibitor LY294002 and the mTOR inhibitor rapamycin to determine the roles of the PI3K/Akt and mTOR signaling pathways. The effects of BMSC-derived exosomes on AECII proliferation and apoptosis were assessed, respectively. Results Decreased levels of the antiapoptotic protein Bcl-2, the cell proliferation protein Ki67, p-PI3K, p-Akt, and p-mTOR, as well as increased levels of AECII apoptosis and the proapoptotic protein Bax in the hyperoxia group were observed. Notably, Sprague Dawley rat BMSC-derived exosomes could reverse the effect of hyperoxia on AECII proliferation. However, the application of LY294002 and rapamycin inhibited the protective effects of BMSC-derived exosomes. Conclusion Our findings revealed that BMSC-derived exosomes could regulate the expression of apoptosis-related proteins likely via the PI3K/Akt/mTOR signaling pathway, thereby preventing hyperoxia-induced AECII apoptosis.
Keywords: Hyperoxia; Exosome; AECIIs; LY294002; Rapamycin; PI3K/Akt/mTOR/Ki67